PENGGUNAAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA SEKOLAH DASAR PADA PEMBELAJARAN IPA - 1)Mar’attus Solihah dan 2)Anggraeni Mashinta (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2019)
AbstractThis study aims to determine the effect of using Problem Based Learning on problem-solving abilities of elementary school students in science learning. The study was conducted in two elementary schools namely Gunungreja Public Elementary School 02 and MI Mafatihul Huda Cipari involving 83 students in the 5th grade. The study design used a non-randomized pretest-posttest design by dividing students in two groups: 42 control group students and 41 treatment group students . The control group is learning the material "digestive system in humans" using conventional methods, while the treatment group uses the Problem Based Learning method. To measure students' problem solving abilities, a test consisting of multiple choices and descriptions is used. The validity and reliability of the instrument were evaluated using expert judgment which was then tested on class VI students of Kalierang State Elementary School 05. To find out the improvement of students 'problem solving abilities in both groups used a t test against normalized gain values of students' problem solving abilities. The results of the data analysis showed differences in the increase in problem solving abilities that were significant between the groups that applied PBL and conventional learning groups.Keywords: Problem Based Learning, problem solving, science learnin